2019
DOI: 10.1038/s41598-019-40007-9
|View full text |Cite
|
Sign up to set email alerts
|

Language Outcomes in Adults with a History of Institutionalization: Behavioral and Neurophysiological Characterization

Abstract: Impoverished early care environments are associated with developmental deficits in children raised in institutional settings. Despite the accumulation of evidence regarding deficits in general cognitive functioning in this population, less is known about the impact of institutionalization on language development at the level of brain and behavior. We examined language outcomes in young adults and adolescents raised in institutions (n = 23) as compared to their socioeconomic status and age peers raised in biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…It is argued that an atypical neural response to semantic incongruity may reflect underspecified lexical representations or altered functional connectivity in children raised in IC in Russia. Data acquired from adults who were raised in institutions in the Russian Federation suggest that detrimental effects of institutionalization can be traced to adulthood and are manifested in atypical N400 and N170 ERP components (Petrov et al, 2018; Kornilov et al, 2019). It has been shown that adults with a history of institutionalization display reduced neural sensitivity to violations of word expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…It is argued that an atypical neural response to semantic incongruity may reflect underspecified lexical representations or altered functional connectivity in children raised in IC in Russia. Data acquired from adults who were raised in institutions in the Russian Federation suggest that detrimental effects of institutionalization can be traced to adulthood and are manifested in atypical N400 and N170 ERP components (Petrov et al, 2018; Kornilov et al, 2019). It has been shown that adults with a history of institutionalization display reduced neural sensitivity to violations of word expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of N400 effect in response to semantic incongruity in the IC group in the current study can be interpreted as an indication of less efficient semantic processing that can result from underspecified lexical representations in children raised in impoverished environments. Results of the previous studies also show decreased N400 effect to semantic incongruity that was registered in semantically overlapping mismatch condition in adults with a history of IC (Kornilov et al., 2019). While the findings of the current study suggest that there are no statistically significant group differences between children in the IC and BFC group with regard to processing semantic incongruity, we hypothesize that the modest sample size might explain our inability to detect group differences; therefore, these findings should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 72%
“…Participants completed a set of behavioral assessments, along with a demographic questionnaire and self‐reported medical history. As in our previous research (Kornilov et al., 2019), we used the Culture‐Fair Intelligence Test, CFIT (Cattell & Cattell, 1973) Scale 2 to assess nonverbal intelligence. This paper and pencil format test contains four timed subtests: a series of subtests assesses the ability to complete a progressive series; in a Classification subtest, participants are asked to mark the item that does not belong with the others; a Matrices subtest requires the individual to mark the item that fits into a pattern; a Conditions subtest, where the respondent selects a geometric drawing that fulfills specified conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies demonstrate that institutional care is associated with a variety of developmental deficits in children and adolescents on a behavioral and neurobiological level (Marshall , Fox, & BEIP Core Group, 2004; Nelson, Fox, & Zeanah, 2014). Negative consequences of IC have been documented for cognitive (Pollak et al., 2010; Wade, Fox, Zeanah, & Nelson, 2019), language (Kornilov et al., 2019), and socio‐emotional (Moulson et al., 2015) domains of development.…”
Section: Introductionmentioning
confidence: 99%